Pengaruh Edukasi Kesehatan Berbasis Flyer Terhadap Pengetahuan Risiko Diabetes Pada Remaja di SMA Negeri 9 Pekanbaru - Putri Arini Hidayah; Abdurrahman Hamid; Mike Ayu Wulandari; Eka Wisanti; Raju Nitrigo (Universitas Hang Tuah Pekanbaru, 2026)
Diabetes mellitus now affects not only adults but also adolescents due to unhealthy eating habits and low understanding of sugar consumption and diabetes-triggering foods, which increase the risk of degenerative diseases from a young age. This study aims to analyze the effect of health education using flyers on diabetes risk knowledge in adolescents. Conducted at SMA Negeri 9 Pekanbaru with a pre-experimental one group pretest–posttest design, involving 34 adolescents in grades 10, 11, and 12 selected through stratified random sampling. Inclusion criteria were active students who were willing to participate in the study, while exclusion criteria were students who did not complete all interventions. The research instruments were a diabetes risk knowledge questionnaire and flyer educational media. Data were collected through a pre-test before the intervention and a post-test after the education was provided, then analyzed using the Wilcoxon test. The results showed an average pre-test of 11.00 and a post-test of 16.00. The Wilcoxon test results showed p = 0.001, which indicated a significant increase in adolescents' knowledge about diabetes risks. The novelty of this research lies in the effectiveness of simple and low-cost educational media to improve adolescent health understanding, as well as scientifically contributing as empirical evidence for the development of school-based preventive health promotion strategies for early prevention of diabetes.